Methods of Account Receivables Recover - Maria Sierpińska (Contemporary Economics)
The paper presents three types of account receivables recover: by court, conciliation, or by financial execution. All of these methods are shortly described and the costs of their using are analyzed. Of course, the mixed method was presented as well. In the article practice of execution firms’ activity in Poland is also shortly presented.